(untitled) (Research, Society and Development, 2020)
Objective: To test the moderating effect of the time perspective on the relationship between socioeconomic status and quality of life of people living with HIV. Method: The data were collected in public health services in Rio de Janeiro and Niteroi, with 281 people, through a questionnaire of socioeconomic data, WHOQOL-HIV bref and ZTPI-25. To identify the moderating effect of the time perspective, multiple linear regression analyzes were performed. Results: The sample was composed mainly of men, education in basic education, income of up to two minimum wages and positive perception of health. The interaction of the time perspective in the assessment of quality of life was observed in the subscales of the past-negative and future, in the physical, psychological, level of independence and spirituality, religion and personal beliefs. The subscales of the time perspective acted as moderators indicating the positive influence of the future on the high scores of quality of life, as well as the low score of the negative past, minimizing the negative effect on quality of life. The moderating effect was not confirmed in the social relations and environment domains of quality of life. Conclusion: The hypothesis that the psychological construct of the time perspective acts as a moderating variable in the relationship between socioeconomic status and quality of life was proven, revealing the importance of the time perspective for the analysis of the quality of life of people living with HIV.